Mecenazgo y escritura en los tiempos de Leandro Fernández de Moratín - Álvarez Barrientos, Joaquín (Cuadernos de Historia Moderna, 2008)
The article focuses on Moratin as a writer bearing in mind a dual perspective. First, the changes in the concepts of “opinion” and “public” at the end of the Early Modern Age in Spain compared with other European countries, and secondly, the relationship between the “men of letters” and the political power.